Autonomous object movement in modeling bees foraging - Theab, Mustafa Muwafak; Yusof, Yuhanis (IEEE Computer Society, 2010)
This paper presents an algorithm inspired by Bresenham's algorithm to move an object from one location to another. This algorithm uses the slope calculation for different location and direction to move an object through the desired path. Such an approach has extended the use of existing Bresenham algorithm into a better use as direction of movement is no longer a limitation. Experiment conducted using Bees simulation environment shows that the required bees have successfully moved to the identified location.